2004
DOI: 10.1111/j.0953-816x.2004.03395.x
|View full text |Cite
|
Sign up to set email alerts
|

The basal ganglia network mediates the planning of movement amplitude

Abstract: This study addresses the hypothesis that the basal ganglia (BG) are involved speci®cally in the planning of movement amplitude (or covariates). Although often advanced, based on observations that Parkinson's disease (PD) patients exhibit hypokinesia in the absence of signi®cant directional errors, this hypothesis has been challenged by a recent alternative, that parkinsonian hypometria could be caused by dysfunction of on-line feedback loops. To re-evaluate this issue, we conducted two successive experiments. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 85 publications
6
73
1
Order By: Relevance
“…Notably absent from our imaging results was the activation of posterior parietal regions, which were previously shown to be involved in tracking errors (Krigolson and Holroyd, 2006) or making on-line corrections (Desmurget et al, 1999(Desmurget et al, , 2004a during continuous motor tasks. Given that in these studies the posterior parietal cortex was said to be implicated in a "low-level" type of control, the lack of activation in our case may indicate that subjects used a higher-level type of control based on prefrontal regions.…”
Section: Discussioncontrasting
confidence: 84%
“…Notably absent from our imaging results was the activation of posterior parietal regions, which were previously shown to be involved in tracking errors (Krigolson and Holroyd, 2006) or making on-line corrections (Desmurget et al, 1999(Desmurget et al, , 2004a during continuous motor tasks. Given that in these studies the posterior parietal cortex was said to be implicated in a "low-level" type of control, the lack of activation in our case may indicate that subjects used a higher-level type of control based on prefrontal regions.…”
Section: Discussioncontrasting
confidence: 84%
“…In contrast, Krakauer et al (2004) found that adaptations to changes in visuomotor gain induced only a subtle increase in rCBF signal in a subset of subcortical motor areas activated in their control task (left insula/putamen, left medial cerebellum, and right putamen) and no significant activation outside of the regions active during the control task. These results are consistent with the proposed role of basal ganglia in scaling the magnitude and rate of increase of muscle activity during movement (Horak and Anderson 1984) and thus in controlling movement extent and velocity (Anderson and Horak 1985;Desmurget et al 2003Desmurget et al , 2004Mazzoni et al 2007;Turner and Anderson 1997;Turner et al 2003). Indeed, inactivation of basal ganglia output pathways in animal models reduces the extent of goal-directed movements but alters neither reaction times (Mink and Thach 1991) nor the normal activation sequence seen during reaching prior to inactivation (Horak and Anderson 1984).…”
Section: Separate Neural Substrates Encoding Movement Direction and Esupporting
confidence: 84%
“…The faulty proprioceptive feedback available caused smaller steps relative to healthy participants because visual confirmation was not available to compensate for the diminished external cueing. Smaller movement amplitude was also noted by Desmurget et al [16], when proprioception was primary source of feedback available to individuals with PD when pointing towards a target, indicating that vision of the limb is required to improve target accuracy.…”
Section: Effect Of Optic Flowsupporting
confidence: 55%